v.4 - All India Congress Committee (New Delhi, 1985)
A Centenary History of the Indian National Congress runs into five volumes, Volume V being the latest, released recently (photo across). Earlier four volumes have been reprinted to make available the comprehensive 5 volume study. The concluding volume of the Centenary History discusses the period, under the aegis of Indira Gandhi, India attained an accelerated pace of development and provided leadership of distinction to the Non-aligned Movement. It also covers the events of 1984 and delineates the new horizons of development under the stewardship of Rajiv Gandhi.
Keywords: Political Parties-India